Female crime in India and theoretical perspectives of crime - Bhosle, Smriti (Delhi : Kalpaz Publications, 2009)
On women offenders and prisoners in jails of Mumbai; a study.
Originally presented as the author's thesis (Ph. D.) under the title: Under-trial female criminals in Mumbai : a sociological study.
Includes statistical tables.
Includes bibliographical references (p. [297]-301) and index.
Keywords: Female offenders -- India -- Mumbai -- Psychology; Women prisoners -- India -- Mumbai -- Social conditions; Jails -- India -- Mumbai -- Social conditions